2016
DOI: 10.1016/j.gene.2016.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Efficient differentiation of murine embryonic stem cells requires the binding of CXXC finger protein 1 to DNA or methylated histone H3-Lys4

Abstract: Mammalian CXXC finger protein 1 (Cfp1) is a DNA-binding protein that is a component of the Setd1 histone methyltransferase complexes and is a critical epigenetic regulator of both histone and cytosine methylation. Murine embryonic stem (ES) cells lacking Cfp1 exhibit a loss of histone H3-Lys4 tri-methylation (H3K4me3) at many CpG islands, and a mis-localization of this epigenetic mark to heterochromatic sub-nuclear domains.Furthermore, these cells fail to undergo cellular differentiation in vitro. These defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Mammalian CFP1 contains an N-terminal PHD domain that recognizes methylated H3K4, a Zn finger CXXC domain that binds to unmethylated CpG dinucleotides, a Set1 interaction domain (SID), a coiled-coiled leucine zipper (LZ) domain, and a cysteine-rich C-terminal domain (Brown et al 2017;Butler et al 2008;Mahadevan and Skalnik 2016;Tate et al 2009;Voo et al 2000)( Figure 2B and S4). C. elegans CFP-1 contains all of these except for the PHD domain.…”
Section: The C-terminal Domain Of Cfp-1 Is Necessary and Sufficient Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian CFP1 contains an N-terminal PHD domain that recognizes methylated H3K4, a Zn finger CXXC domain that binds to unmethylated CpG dinucleotides, a Set1 interaction domain (SID), a coiled-coiled leucine zipper (LZ) domain, and a cysteine-rich C-terminal domain (Brown et al 2017;Butler et al 2008;Mahadevan and Skalnik 2016;Tate et al 2009;Voo et al 2000)( Figure 2B and S4). C. elegans CFP-1 contains all of these except for the PHD domain.…”
Section: The C-terminal Domain Of Cfp-1 Is Necessary and Sufficient Fmentioning
confidence: 99%
“…The CFP1/CXXC zinc finger protein targets the SET1/COMPASS complex to non-methylated CpG rich regions for trimethylation of histone H3 on Lys4 (H3K4me3) (Brown et al 2017;Clouaire et al 2012;Lee and Skalnik 2005;Mahadevan and Skalnik 2016;Thomson et al 2010), a modification widely associated with active promoters (Bernstein et al 2005;Heintzman et al 2007;Schneider et al 2004). The roles of CFP1 and the SET1/COMPASS complex in gene regulation are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a global reduction in DNA methylation was also observed, most likely due to reduced expression of DNMT1 [76]. Differentiation cannot occur in these CFP1−/− ES cells, but rescue of the knockout ES cells with different CFP1 mutants indicates that either the PHD domain binding to H3K4me1/2/3 or the CpG binding activity are required to restore H3K4me distribution and ES differentiation [75]. One of the remarkable observations from CFP1−/− ES cells is that although the most highly expressed genes are those that suffer the greatest H3K4me3 loss, yet significant loss of transcription at those loci did not occur [74].…”
Section: Setd1a/setd1b In Hematopoiesis and Leukemiamentioning
confidence: 97%
“…For example, by knocking out the CFP1 (also called CXXC protein, binds non-methylated CpGs) in murine ES cells, H3K4me3 peak reduction was observed at about 50 % of TSSs. Furthermore, H3K4me3 is acquired in nuclear territories and regions of the genome in which it does not appear in wild-type cells, resulting in ectopic transcription [74,75]. Therefore, CFP1 is critical for directing H3K4 methylation activity to proper genomic locations.…”
Section: Setd1a/setd1b In Hematopoiesis and Leukemiamentioning
confidence: 99%
“…CFP1 binds to unmethylated CpG-rich DNA sequences known as CpG islands (CGIs) and helps the recruitment of SET1/COMPASS complex at the promoter region of active genes (Chun et al, 2014, Chen et al, 2014, Thomson et al, 2010, Clouaire et al, 2012, Tate et al, 2010. Previous studies have reported that CFP1 plays an important role in cell fate specification and cell differentiation (Clouaire et al, 2014, Mahadevan and Skalnik, 2016, Skalnik, 2010. However, the exact mechanism by which CFP1 contributes to gene regulation and development is not clear.…”
Section: Introductionmentioning
confidence: 99%